Implementasi pendidikan karakter di MTs Negeri Kabupaten Klaten - Sri Hartini; Maragustam Siregar; Ahmad Arifi (Universitas Muhammadiyah Ponorogo, 2020)
Character is mental characteristics and morals that exist in a person. Besides character is also interpreted as ownership of good things. The goodness is like honesty, courage, justice, and compassion. Character education is a deliberate/conscious effort to realize virtue, that is a good quality of humanity objectively, not only good for individual individuals, but also good for society as a whole. This study aims to: Know the problems of character education in terms of micro, meso, and macro approaches. Knowing the implementation of character education according to the three approaches of micro, meso, and macro. Knowing the reason for the need for character education is carried out in MTs Negeri Klaten Regency. Knowing the results of the implementation of character education according to three approaches to micro, meso, and macro. This research uses a qualitative approach. The subjects of this study were the Head of Madrasah, Deputy Head of Madrasa in the field of curriculum, Deputy Head of Madrasa in Student Affairs, Counseling Guidance Teacher and students. Data collection techniques in the form of observation, interviews and documentation. Analysis of the data in this study used the data analysis technique of the Miles and Huberman model. The results showed: 1) The implementation of the micro aspect was carried out by the madrasah steakholder, the meso aspect by building madrasa culture, while the macro aspect was working with parents of the parents. 2) The results of the implementation of character education that have been developed each contribute to the madrasa, namely the improvement of better student character.